Strategic Deployment of Drone in Combating Insecurity in Africa - Okwara, Emmanuel Chukwuma (Kashere Journal of Politics and International Relations, 2025)
Insecuity remains one of the most pressing challenges facing Africa, with persistent threats from terrorism, insurgency, banditry, and transnational organized crime. In response, many African states are increasingly turning to advanced technologies, particularly drones, as part of a strategic shift in security operations. This paper examines the strategic deployment of drones in combating insecurity across the continent, highlighting their roles in surveillance, reconnaissance, target acquisition, and tactical operations. Drawing on examples from Nigeria, Somalia, and the Sahel region, the study assesses how drones have improved intelligence gathering, enhanced operational precision, and minimized risks to military personnel. Despite these advantages, the deployment of drones is constrained by issues such as high procurement costs, limited technical capacity, inadequate legal frameworks, and ethical concerns surrounding civilian oversight and data privacy. The paper argues that while drones are not a standalone solution, their integration into national and regional security strategies alongside traditional forces and community-based initiatives can significantly enhance the effectiveness of security interventions. It concludes by recommending increased investment in local drone technology, capacity building, and regional collaboration to ensure sustainable and accountable use of drones in promoting peace and stability in Africa.